Hydrogen embrittlement of tungsten induced by deuterium plasma: Insights from nanoindentation tests. Issue 20 (29th October 2018) - Fang, Xufei; Kreter, Arkadi; Rasinski, Marcin; Kirchlechner, Christoph; Brinckmann, Steffen; Linsmeier, Christian; Dehm, Gerhard
Abstract: Abstract : Hydrogen exposure has been found to result in metal embrittlement. In this work, we use nanoindentation to study the mechanical properties of polycrystalline tungsten subjected to deuterium plasma exposure. For the purpose of comparison, nanoindentation tests on exposed and unexposed reference tungsten were carried out. The results exhibit a decrease in the pop-in load and an increase in hardness on the exposed tungsten sample after deuterium exposure. No significant influence of grain orientation on the pop-in load was observed. After a desorption time of t d ≥ 168 h, both the pop-in load and hardness exhibit a recovering trend toward the reference state without deuterium exposure. The decrease of pop-in load is explained using the defactant theory, which suggests that the presence of deuterium facilitates the dislocation nucleation. The increase of hardness is discussed based on two possible mechanisms of the defactant theory and hydrogen pinning of dislocations.